Тактика і методика розслідування корупційних злочинів - Мезенцева, І.Є. (Криміналістика і судова експертиза, 2017)
The article analyzes tactics and methodology for investigating corruption crimes. It characterizes the existing inconsistencies and discrepancies between criminal law and criminal procedure norms that complicate proof in criminal proceedings on corruption offenses. The significance of digital evidence and computer-technical examination for proving guilt or involvement of a person in corruption is determined.